Nutrients Suspended Solid and Organic Matter Removal From River Water Using Sugarcane Fibres (Bagasse) - Low, Ying Binng (2018)
The adoption of agriculture waste materials as alternative adsorbent has become an attractive option because of its low cost and availability. The utilization of agriculture waste material such as Sugarcane Bagasse (SCB) can help reducing waste problems and therefore beneficial to the environment. This study presents the investigation of Sugarcane Bagasse as an alternative adsorbent used for river water treatment and it enclosed the evaluation of adsorption efficiency of SCB for nitrate, phosphate, total suspended solid, biological oxygen demand and chemical oxygen demand by the means of calculation of adsorption capacity and percentage removal of each pollutant. The performance of adsorption by manipulating the flow rate of water is studied and the comparison on pollutant’s concentration level based on INWQS is also discussed in project. The techniques used in this project is adsorbent as filtration media whereby water will be circulated using prototype for three consecutive days. The results shows that the percentage removal of nitrate and phosphate for low flow rate are 88.52% and 7.69 % whereas for total suspended solid is 86.75%. The percentage removal for nitrate, phosphate and total suspended solid for high flow is found to be 92.94%, 33.33% and 92.21% respectively. It was observed that both high and low flow rate shows a reduction in pollutants concentration level and both adsorption capacity and percentage removal of pollutants are greater at high flow rate. The usage of SCB as adsorbent would contribute to alternative low cost adsorbent usage and reduce the agriculture waste disposed to the landfills.